The subjective perception of the happiness of older adult residents in Colombia - Segura, Alejandra; Cardona, Doris; Segura, Angela; Robledo, Carlos Arturo; Muñoz, Diana Isabel (Frontiers in Medicine, 2023)
Abstract Happiness is an affective state of satisfaction that everyone wants to achieve in the different stages of life. It is considered that in old age the perception of happiness is fueled by the achievements and triumphs; however, there are factors that influence this ideal. Objective analyze the factors associated with the subjective perception of happiness in the elderly, using data from a study conducted in five cities in Colombia. Materials and methods Quantitative, cross-sectional study, with a primary information source obtained from 2506 surveys carried out on people aged 60 and over who participated voluntarily, without cognitive impairment, and who reside in urban areas except in long-term centers. The variable "happiness" was measured with the Alarcón scale and using it conducted: 1) the characterization of the elderly, 2) a bivariate exploration: the estimation of the relationships with the factors studied, and 3) a multivariate exploration: construction of profiles through multiple correspondences. Results 67.2% reported high happiness levels, with differences by city studied (happiness between 48.7% and 81.6). Likewise, happiness, explained by not presenting a risk of depression asymptomatic to hopelessness, strengthened their psychological well-being, a perception of high quality of life, and living in a functional family. Conclusions This study provided a systematic overview of the possible factors that can be enhanced and strengthened with public policies (structural determinant), community empowerment, family strengthening (intermediate determinant), and educational programs (proximal determinant), aspects included in the essential functions of public health, in favor of the mental and social health of the elderly.